Formalism in Architecture and its Relation with the Concept of Form - Mona Bolouri Bazzaz; Alireza Mostaghni (صفه)
The concept of "form" is among the most important concepts in the present-day architectural discourse. There is also a thought and an approach called formalism in architecture, which basically focuses on the form of the work in the absence of functional, social, and other considerations. Form is the core concept in the formalist thought; yet its countless significations on one hand, and the lack of well-organised research on its origins on the other, have hindered an understanding of the essence of formalist thought especially when it comes to architecture. The present paper studies architectural formalist thought, and attempts to find the kind of understanding of form involved there. Formalism is seen here not as an intervention approach for architects but a mode of thought among architectural scholars, critics and theoreticians. The study here is through literature on formalism and form in architecture. The architectural formalist thought has its roots in artistic currents, and is thus informed by them, and in turn influencing architectural scholars, critics and theoreticians. Three types of formalism are recognised here: formalism as a thought possessed by architectural scholars in the realm of architectural theory, formalism as a method for the analysis of architectural works, and formalism as a design method. The paper particularly focuses on formalism in the realm of architectural theory.